Experimental investigation of stability and extinction coefficient of Al2O3–CuO binary nanoparticles dispersed in ethylene glycol–water mixture for low-temperature direct absorption solar collectors. (15th January 2016) - Menbari, Amir; Alemrajabi, Ali Akbar; Ghayeb, Yousef
Highlights: Viscosity and optical properties of binary nanofluids are investigated. Effective parameters on stability of binary nanofluids are studied. At optimal stability condition viscosity and absorbency of nanofluids are optimum. The extinction coefficient of binary nanofluids is sum of its components ones. Abstract: Binary nanofluids form a new class of nanofluids made through the simultaneous dispersion of two dissimilar nanoparticles in a base fluid. Two different nanoparticles may behave differently from their constituent components. Given the wide applications of binary nanofluids in a variety of fields, it is important to gain an understanding of the best stability conditions for binary nanofluids. In this work, the effects of such nanofluid properties as pH, surfactant (SHMP) concentration, and ultrasonic time are experimentally investigated on the stability of binary nanofluids. For this purpose, binary nanofluids are prepared using the two-step method. Two dissimilar nanoparticles, i.e. CuO and γ-Al2 O3 nanoparticles are dispersed in ethylene glycol and in the ethylene glycol–water mixture to form the desired nanofluids. Results show that at optimal stability conditions, viscosity and absorbency of the nanofluids are minimum and maximum, respectively. Also, the stability optimal parameters of binary nanofluids are found to be different from their corresponding values for each individual nanofluid. The extinction coefficient of the binary nanofluid is found to be approximately equal to the sum of those of the constituent components. Finally, the extinction coefficient of the nanoparticles dispersed in the mixture of ethylene glycol–water is determined to be greater than that of ethylene glycol.